Determinants and Challenges of SAK EMKM Implementation in MSME Financial Reporting: A Systematic Literature Review - Lazarus Suyatno Vianney; Debi Dince Yoweni; Cliford Racelino Ratulang; Matilda Serfi Desta; Raymond Piring (Journal of Educational Management Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting economic development; however, the effectiveness of their financial governance remains a major concern, particularly regarding the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This study aims to examine the implementation of SAK EMKM among MSMEs, identify the main challenges affecting its adoption, and formulate strategies to strengthen financial reporting practices. This study employed a Systematic Literature Review (SLR) approach by analyzing relevant scientific articles related to SAK EMKM implementation and the factors influencing its adoption. The findings reveal that although MSMEs have increasingly recognized the importance of financial record-keeping, the implementation of SAK EMKM remains limited because many businesses still rely on simple bookkeeping practices. The main challenges include inadequate accounting literacy, limited human resource competence, insufficient training and mentoring, low utilization of information technology, and weak institutional support. This study implies that improving SAK EMKM implementation requires integrated strategies involving accounting education, continuous assistance, digital financial management adoption, and stronger collaboration among stakeholders to enhance the quality of MSME financial reporting and business sustainability.